On the existence of a solution of a quasilinear mixed problem for a quasiwave equation - Kolomiyets, V. G.; Komashinskaya, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We establish conditions for the existence and uniqueness of a solution of a quasilinear mixed problem for a quasiwave equation.